Conjunctival sac microbiome in anophthalmic patients: Flora diversity and the impact of ocular prosthesis materials - Zhao, Hejia; Chen, Yanjun; Zheng, Yixu; Xu, Jing; Zhang, Chenyu; Fu, Min; Xiong, Ke (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose To explore the changes of bacterial flora in anophthalmic patients wearing ocular prosthesis (OP) and the microbiome diversity in conditions of different OP materials. Methods A cross-sectional clinical study was conducted, involving 19 OP patients and 23 healthy subjects. Samples were collected from the upper, lower palpebral, caruncle, and fornix conjunctiva. 16S rRNA sequencing was applied to identify the bacterial flora in the samples. The eye comfort of each OP patient was determined by a questionnaire. In addition, demographics information of each participant was also collected. Results The diversity and richness of ocular flora in OP patients were significantly higher than that in healthy subjects. The results of flora species analysis also indicated that in OP patients, pathogenic microorganisms such as Escherichia Shigella and Fusobacterium increased significantly, while the resident flora of Lactobacillus and Lactococcus decreased significantly. Within the self-comparison of OP patients, compared with Polymethyl Methacrylate (PMMA), prosthetic material of glass will lead to the increased colonization of opportunistic pathogens such as Alcaligenes, Dermabacter and Spirochaetes, while gender and age have no significant impact on ocular flora. Conclusions The ocular flora of OP patients was significantly different from that of healthy people. Abundant colonization of pathogenic microorganisms may have an important potential relationship with eye discomfort and eye diseases of OP patients. PMMA, as an artificial eye material, demonstrated potential advantages in reducing the colonization of opportunistic pathogens.